Contemporary Logistics in China Consolidation and Deepening - Liu, Bing-lian.; Liu, Bing-lian.; Lee, Shao-ju.; Lee, Shao-ju.; Wang, Ling.; Wang, Ling.; Li, Xiang.; Li, Xiang.; Xiao, Jian-hua.; Xiao, Jian-hua. (Current Chinese Economic Report Series, 2014)
While logistics has caught on as a vital component in China’s national development plan, both government agencies at all levels and various types of enterprises have put considerable effort into propelling logistics to a new height.  Recent logistics developments in China have witnessed a scene of significant boom dotted with few sporadic dips. This book, the third volume in the series on “Contemporary Logistics in China,” is a must-read publication, which affords the readers a clearer view of the intrinsic consolidation and  increased efforts made amid the recent advancements in China’s logistics development. The research findings in this book reflect the expertise and diligence of a team of learned researchers in the highly-regarded Logistics Research Center at Nankai University. The book presents a comprehensive and thorough analysis of the progression and propagation of modern logistics in China, as well as a fresh look at some emerging hot issues with potential bearings on future logistics development. Researchers and practicing professionals alike will find this book an indispensable and timely reference and information resource.